2009
DOI: 10.1017/s1481803500011210
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine as a career choice: a descriptive study of Canadian medical students

Abstract: Background: Studies indicate that a student's career interest at medical school entry is related to his or her ultimate career. We sought to determine the level of interest in emergency medicine among students at the time of medical school entry, and to describe characteristics associated with students primarily interested in emergency medicine. Methods: We surveyed students in 18 medical school classes from 8 Canadian universities between 2001 and 2004 at the commencement of their studies. Participants listed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 27 publications
(23 reference statements)
1
39
1
Order By: Relevance
“…(8) Other important influencing factors found in the same Canadian study include the wide variety of patient problems and interesting patient population. (8) In the United States, the most important factors for applicants choosing a specialty lifestyle were mentors and role models, and length of residency.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…(8) Other important influencing factors found in the same Canadian study include the wide variety of patient problems and interesting patient population. (8) In the United States, the most important factors for applicants choosing a specialty lifestyle were mentors and role models, and length of residency.…”
Section: Discussionmentioning
confidence: 85%
“…(8) Other important influencing factors found in the same Canadian study include the wide variety of patient problems and interesting patient population. (8) In the United States, the most important factors for applicants choosing a specialty lifestyle were mentors and role models, and length of residency. (6) A local study on postgraduate specialty in medical students showed that 95% of respondents rated 'compatibility between personality and speciality' as being influential in specialty choice, while another local study on subspecialty selection in internal medicine revealed lifestyle factors, programme characteristics and reputation, and burnout to be important influencing factors.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Multitasking, dealing with interruptions, and managing numerous patients simultaneously are key skills in EPs' work lives. [1] Previous studies have revealed that variety in clinical pathology, emphasis on acute care, previous work in an emergency setting, and fl exibility both in terms of practice location and work schedule are the main factors in EPs' career selection. [2] Career longevity, job satisfaction, and burnout among EPs are areas of debate.…”
Section: Introductionmentioning
confidence: 99%
“…In other publications, EM is described as a very attractive specialty among medical students, 7 largely because of clinical factors (e.g., diversity of clinical pathology and emphasis on acute care) and because it allows for a controllable lifestyle. 8,9 EM is considered a lifestyle specialty 8,9 with predictable hours and a balance among clinical work, administrative duties, organizational commitments, teaching, and/or research. Offering this vast range of activities is only possible when a specialty has reached its critical mass of practitioners, allowing them some "off clinical" time.…”
Section: Discussionmentioning
confidence: 99%